Analisis dan Perancangan Sistem Informasi Manajemen BUMDes Berbasis Website Menggunakan Standar ISO/IEC 25010 - Aldy Bifal Pratama; Muhamad Andri Rian Riyadi; Chairul Anwar (Journal of Information Systems and Business Technology, 2026)
The village economy is strategically driven by village-owned enterprises (BUMDes), but accountability and transparency are frequently hampered by manual data administration. The analysis and construction of a web-based BUMDes Management Information System are the goals of this project. Digitising the company's inventory, financial reporting, and administrative procedures is the aim. Because it enables BUMDes developers and managers to work closely together to identify user demands by gradually iterating the interface and functionality design, the prototype system development method was used for this study. By doing this, the likelihood of system incompatibility during the last step of implementation is decreased.The international standard ISO/IEC 25010 is used to guarantee the quality of the software produced. The primary subjects of testing are functional suitability, performance efficiency, ease of use, and reliability. A systematic and scalable information system model that may enhance BUMDes operations' efficiency and support data-driven decision-making is anticipated as a result of this design.